(untitled) (Journal of Hama University, 2022)
The research aimed to assess the weight effect and duration of storage of incubation eggs at the age and weight of birds at the sexual maturity of Japanese Quail, and the study was conducted on 360 eggs divided into two experiments: the first experiment by Gw egg weight (180 eggs) divided into 3 T1ws (small eggs less than 10g) T2wm (average eggs 10-12g), T3wb (large eggs>12g), and the second experiment by Gd egg storage period (180 eggs) also divided into 3 treatments (3-day store)Td3, (store For 7 days)Td7, (10-day store) Td10, per treatment 3 repeaters (each repeater 20 eggs). The eggs were incubated in optimal conditions for 17 days and with the hatching process completed the chicks were transferred to a farm, where they were cared for in optimal conditions for 45 days. The study showed a significant effect (P<0.05) of egg weight at the sexual maturity age of Japanese quail male and female chicks, with t1ws recording a delay in sexual maturity (34.70 days) (43.26 days) for males and females, respectively, with a significant decrease in the weight at the sexual maturity (130.2g), (204.1g), respectively. The results also showed that storing eggs for no more than 3 days gave early males sexual maturity (33.45) days, weight (160.40 g), as well as early-maturing females (42.26) days with a weight (245.60 g), compared to eggs stored for 7-10 days, which resulted in females and males late in sexual maturity and a decrease in body weight.